P.122 Unbiased whole brain circuit interrogation reveals neurons restoring walking after spinal cord injury. (June 2022) - Cho, N; Squair, J; James, N; Baud, L; Leonhartsberger, A; Sveistyte, K; Galan, K; Barraud, Q; Goubran, M; Batti, L; Pages, S; Gautier, M; et al.
Abstract : Background: There is presently no cure for locomotor deficits after spinal cord injury (SCI). Very few therapies effectively target the brain due to poor understanding of the brain's role post-SCI. Newly developed tissue clearing techniques have permitted unbiased three-dimensional circuit analysis, opening new opportunities for SCI-related brain interrogation. Methods: We established a novel brain interrogation pipeline by optimizing mouse brain clearing, imaging, and atlas registration. We leveraged a spontaneous recovery lateral hemisection model to analyze whole brain cell activity and connectivity with the lumbar cord using cFos immunolabelling and virus-mediated projection tracing. We identified a functionally and anatomically dynamic region correlating with recovery and interrogated its locomotor role with optogenetics. We assessed deep brain electrical stimulation (DBS) of this region in a more clinically relevant rat contusion SCI using an established bipedal robotic interface. Results: We unexpectedly uncovered the lateral hypothalamus (LH) to functionally and anatomically correlate with recovery. LH Vglut2 optogenetic stimulation significantly augmented locomotor function. LH DBS in rats acutely robustly augmented bipedal locomotion post-SCI. Conclusions: This is the first demonstration of the LH's role in locomotion post-SCI and is a novel DBS target that robustly augmented locomotor function, dependent on LH glutamatergic cells. LH DBS may be a promising intervention in humans.